Education, Knowledge, and Practice Characteristics of Cannabis Physicians: A Survey of the Society of Cannabis Clinicians - Takakuwa, Kevin M. (Cannabis Cannabinoid Res, 2021)
Context: Medical cannabis use has increased in recent years despite being a federally illegal drug in the United States. States with medical cannabis use laws require patients to be certified by physicians. However, little is known about the education, knowledge, and practice characteristics of physicians who recommend and supervise patients' use of medical cannabis. Objective: This study assessed how U.S. physicians who practice cannabis medicine are educated, self-assess their knowledge, and describe their practice. Methods: In fall 2017, a 57-item, electronic survey was sent to all members of the Society of Cannabis Clinicians. Because California has had legalized medical cannabis for longer than any other state, we analyzed responses for 14 items between California and non-California physicians. Results: Of 282 surveyed, 133 were eligible and 45 completed the survey. Of those, multiple medical specialties were represented. Only one physician received education during medical school about cannabis medicine, but physicians gained knowledge through conferences (71%, 32/45), the medical literature (64%, 29/45), and websites (62%, 28/45). Just over half (56%, 20/45) felt that there was sufficient information available to practice cannabis medicine. Of the 37 who answered the knowledge question, most felt knowledgable about cannabinoids (78%, 29/37) and the endocannabinoid system (76%, 28/37). There was a wide variation in the number of cannabis recommendations provided by physicians over the course of their practice career (median 1200; interquartile range, 100–5000), and most provided condition-specific treatment (69%, 31/45) and dosing recommendations (62%, 28/45). The majority (81%, 30/37) of physicians received referrals from mainstream medical providers. No differences were found between California and non-California physicians, except more women were from California (p=0.02). Conclusions: The use of medical cannabis continues to increase in the United States and globally. All states that allow medical cannabis require a physician's recommendation, yet few states require specific clinical training. Findings of this study suggest the need for more formal education and training of physicians in medical school and residency, more opportunities for cannabis-related continuing medical education for practicing physicians, and clinical and basic science research that will inform best practices in cannabis medicine.